Cholinergic enhancement differentially modulates neural response to encoding during face identity and face location working memory tasks. (September 2013) - Handjaras, Giacomo; Ricciardi, Emiliano; Szczepanik, Joanna; Pietrini, Pietro; Furey, Maura L
Potentiation of cholinergic transmission influences stimulus processing by enhancing signal detection through suppression and/or filtering out of irrelevant information (bottom-up modulation) and with top-down task-oriented executive mechanisms based on the recruitment of prefrontal and parietal attentional systems. The cholinergic system also plays a critical role in working memory (WM) processes and preferentially modulates WM encoding, likely through stimulus-processing mechanisms. Previous research reported increased brain responses in visual extrastriate cortical regions during cholinergic enhancement in the encoding phase of WM, independently addressing object and spatial encoding. The current study used functional magnetic resonance imaging to determine the effects of cholinergic enhancement on encoding of key visual processing features. Subjects participated in two scanning sessions, one during an intravenous (i.v.) infusion of saline and the other during an infusion of the acetylcholinesterase inhibitor physostigmine. In each scan session, subjects alternated between a face identity recognition and a spatial location WM. Enhanced cholinergic function increased neural activity in the ventral stream during encoding of face identity and in the dorsal stream during encoding of face location. Conversely, a reduction in brain response was found for scrambled sensorimotor control images. The cholinergic effects on neural activity in the ventral stream during encoding of face identity were stronger than those observed in the dorsal stream during encoding of face location, likely as a consequence of the role of acetylcholine in establishing the inherently relevant nature of face identity. Despite the limited sample-size, the results suggest the stimulus-dependent role of cholinergic system in signal detection, as they show that cholinergic potentiation enhances neural activity in regions associated with early perceptual processing in a selective manner depending on the attended stimulus feature.